2022
DOI: 10.1530/eor-22-0001
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary nailing for impending or pathologic fracture of the long bone: titanium vs carbon fiber peek nailing

Abstract: Purpose The aim of this study is to compare titanium vs carbon fiber intramedullary (IM) nailing in terms of response to radiotherapy, local control of the disease, time of surgery, fluoroscopy exposure, and complications. Methods From 2015 to 2021, 52 impending or pathologic fractures were treated with IM nailing in 47 patients: 18 males and 29 females with a mean age of 73. Titanium nails were used in 27 cases: femur (17 cases), humerus (8 cases), and tibia (2 cases). Carbon fiber nails were used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…In contrast, according to Pala et al, the heightened elasticity of a carbon fiber polymer might permit substantial movement, probably with a higher risk of delayed union and nonunion: their study demonstrated a high incidence of implant failure and nonunion (31% non-union rate) when CFR nails were employed in corrective osteotomies for lower limb deformities [25].…”
Section: Biomechanical Propertiesmentioning
confidence: 88%
See 2 more Smart Citations
“…In contrast, according to Pala et al, the heightened elasticity of a carbon fiber polymer might permit substantial movement, probably with a higher risk of delayed union and nonunion: their study demonstrated a high incidence of implant failure and nonunion (31% non-union rate) when CFR nails were employed in corrective osteotomies for lower limb deformities [25].…”
Section: Biomechanical Propertiesmentioning
confidence: 88%
“…Carbon fiber nails exhibit low artifact levels, allowing radiotherapists to administer a more effective dose with reduced risks for the patient [25]. This characteristic underscores the potential benefits of CFR implants in the management of oncological patients undergoing radiotherapy [14].…”
Section: Intramedullary Implantsmentioning
confidence: 93%
See 1 more Smart Citation
“…It can make difficult the bone healing or other complications evaluation during the follow-up. In addition, carbon fiber constructs have an elastic modularity more like bone cortex than titanium: it can improve the resistance to mechanical stress and bring to a faster recovery [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…CFR-PEEK nails seem to be a good solution in patients with pathologic or impending fractures of the long bones [24]. No matter of life expectancy, studies suggest that either intramedullary nailing or plate fixation with bone cement augmentation and radiotherapy for pathological fractures of the humerus shaft are safe ways to improve quality of life and arm function [25][26][27][28][29][30].…”
Section: Case Reportmentioning
confidence: 99%